2008
DOI: 10.1104/pp.108.124404
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Interacts with Salicylate to Regulate Biphasic Ethylene Production during the Hypersensitive Response

Abstract: C2H4 is associated with plant defense, but its role during the hypersensitive response (HR) remains largely uncharacterized. C2H4 production in tobacco (Nicotiana tabacum) following inoculation with HR-eliciting Pseudomonas syringae pathovars measured by laser photoacoustic detection was biphasic. A first transient rise (C2H4-I) occurred 1 to 4 h following inoculation with HR-eliciting, disease-forming, and nonpathogenic strains and also with flagellin (flg22). A second (avirulence-dependent) rise, at approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 77 publications
7
85
0
1
Order By: Relevance
“…The reciprocal control of NO and SA over each other was found to affect the ethylene metabolism in turn, which influenced the pattern of defense responses in tobacco, revealing the reciprocal antagonistic interplay of NO and ethylene. 65 In addition, NO and ROS redox signaling networks were affected by SA during biotic stress. 66 SA accumulation triggered by NO was found to suppress superoxide free radical and other ROS production 67 and thereby aiding in the maintenance of cell membrane integrity and tissue senescence.…”
Section: +mentioning
confidence: 99%
“…The reciprocal control of NO and SA over each other was found to affect the ethylene metabolism in turn, which influenced the pattern of defense responses in tobacco, revealing the reciprocal antagonistic interplay of NO and ethylene. 65 In addition, NO and ROS redox signaling networks were affected by SA during biotic stress. 66 SA accumulation triggered by NO was found to suppress superoxide free radical and other ROS production 67 and thereby aiding in the maintenance of cell membrane integrity and tissue senescence.…”
Section: +mentioning
confidence: 99%
“…Conversely, ethylene is a virulence factor of many biotropic or semibiotrophic pathogens (Mur et al, 2008). Further, a previous study reported that ethylene production in tobacco (Nicotiana tabacum) leaves after inoculation with HR-inducing Pseudomonas syringae follows a biphasic pattern reminiscent of H 2 O 2 production (Mur et al, 2008). However, P. syringae pv tabaci, which causes disease symptoms in tobacco, elicits only a single peak in ethylene production.…”
mentioning
confidence: 99%
“…It was demonstrated in an analysis of ethylene-insensitive2 (ein2) mutant in Arabidopsis (Arabidopsis thaliana) that ethylene plays, at best, a minor role in hypersensitive response (HR)-mediated cell death. Conversely, ethylene is a virulence factor of many biotropic or semibiotrophic pathogens (Mur et al, 2008). Further, a previous study reported that ethylene production in tobacco (Nicotiana tabacum) leaves after inoculation with HR-inducing Pseudomonas syringae follows a biphasic pattern reminiscent of H 2 O 2 production (Mur et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…El NO regula estos procesos, al menos en parte, mediante la interacción con las rutas de señalización de las diferentes hormonas (Delledonne et al, 1998;Dangl 1998;Tun et al, 2001;Desikan et al, 2002;Beligni et al, 2002;OrozcoCardenas y Ryan 2002;Guo et al, 2003;Pagnussat et al, 2004;Huang et al, 2004;Jovanovic et al, 2005;Bethke et al, 2006a;Lindermayr et al, 2006;Tun et al, 2006;Groppa et al, 2008). De una forma paralela, se ha descrito tanto la producción de NO tras la aplicación de diferentes hormonas como las auxinas (Pagnussat et al, 2002;Pagnussat et al, 2003;Kolbert et al, 2008b;a), citoquininas (Tun et al, 2001;Tun et al, 2008), ABA (Neill et al, 2002a;Bright et al, 2006), SA (Zottini et al, 2007), JA , GAs (Bethke et al, 2004a) y poliaminas (Tun et al, 2006), como la modulación de los niveles de diferentes hormonas por NO Xu et al, 2005;Gniazdowska et al, 2007;Mur et al, 2008;Liu et al, 2009b).…”
Section: Introductionunclassified